A precise deconvolution method to derive methane hydrate cage occupancy ratios using Raman spectroscopy. (16th March 2020) - Hiraga, Yuya; Sasagawa, Takuya; Yamamoto, Shinichiro; Komatsu, Hiroyuki; Ota, Masaki; Tsukada, Takao; Smith, Richard L.
Graphical abstract: Abstract: Raman spectroscopy was used to analyze cage occupancy of thin homogeneous methane hydrate (MH) films at (2.9 to 7.6) MPa and (273 to 276) K. The MH films were synthesized on the lower surface of a sapphire window of a high-pressure cell to eliminate noise associated with the CH stretching vibration of bulk methane gas. Methane medium-size to small-size cage occupancy ratios of the MH films were determined for purposes of assessing the reliability of deconvolution functions used in data reduction. Gaussian, Lorentzian and Voigt functions were considered and the Voigt function was found to provide the most reliable function in terms of fitting precision. Methane occupancy ratios tend to decrease with increasing pressure which is important for practical scale simulations.